Does Corporate Performance Mediate the Relationship Between ESG Risks and Foreign Ownership? Evidence from Saudi-Listed Companies - Chaabouni, Ines (Journal of Posthumanism, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) Risk on foreign ownership of Saudi-listed companies, with corporate performance serving as a potential mediator. Using 2023 data from 117 listed companies on the Saudi Stock Exchange, we investigate whether ESG risk scores influence foreign investors' decisions and whether return on equity (ROE) mediates this influence. The findings suggest a high negative correlation between foreign ownership and ESG risk in a way that foreigners least desire firms with higher ESG risks. While ESG risk negatively affects ROE, its statistically non-significant mediating effect on foreign ownership exists. Also, Board size positively affects foreign ownership by reflecting the structural function of boards in welcoming outsiders. Bootstrap test of robustness confirms that the indirect effect of ROE is insignificant. The study contributes to the expanding literature on foreign investment and ESG by asserting the direct role of ESG risk on the investor's behavior.